2022
DOI: 10.1177/00034894221104461
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Ciprofloxacin/Dexamethasone Drops in the Pediatric Upper Airway: Case Presentation and Review of Adverse Effects

Abstract: Objective: This report describes a new observation of hyperglycemia in a child with Type 1 diabetes after off-label use of otic ciprofloxacin/dexamethasone drops in the nasal passage and reviews previous reports of adverse endocrine effects from intranasal corticosteroids in pediatric patients. Methods: We describe the clinical case and conducted a literature review of MEDLINE (PubMed) and EMBASE. Results: A 9-month-old female with a history of Type 1 diabetes who underwent unilateral choanal atresia repair wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Ben-Dov et al reported the use of CPD off-label to prevent postoperative granulation after choanal atresia repair in an infant. 15 One potential explanation for the limited data on the use of CPD or other nebulized antibiotic-steroid combinations may be that because these medications are so effective that clinicians may not feel comfortable omitting their use solely for research purposes. Given this, our survey results provide insights into the numerous indications for which pediatric otolaryngologists are commonly using CPD off-label.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ben-Dov et al reported the use of CPD off-label to prevent postoperative granulation after choanal atresia repair in an infant. 15 One potential explanation for the limited data on the use of CPD or other nebulized antibiotic-steroid combinations may be that because these medications are so effective that clinicians may not feel comfortable omitting their use solely for research purposes. Given this, our survey results provide insights into the numerous indications for which pediatric otolaryngologists are commonly using CPD off-label.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common indication was choanal atresia, reported by 82.1% of respondents. Ben‐Dov et al reported the use of CPD off‐label to prevent postoperative granulation after choanal atresia repair in an infant 15 . One potential explanation for the limited data on the use of CPD or other nebulized antibiotic‐steroid combinations may be that because these medications are so effective that clinicians may not feel comfortable omitting their use solely for research purposes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations